Developing Basic Writing Module: Paper Based and Android Based Operating System for Second Semester at University of Muhammadiyah Gresik - Karimah, Nur Alfin (Jetlal, 2019)
The objective of this study is to develop Basic Writing module, both paper based and digital form for second semester English Education Department student at University of Muhammadiyah Gresik. The principle of discovery learning is used as the design of module content based on SCL (Student Centred Learning) approach for realizing active learning environment. This research uses Research and Development (R & D) as the design. The development model is adapted based on Branch (2009) model. It covers five steps of ADDIE (Analyze, Design, Develop, Implement, and Evaluate). To collect the data, the researcher used some instruments, i.e. interview question list, need analysis questionnaire, experts judgment questionnaires, and student response questionnaire. The results of this study are: 1) The students use English in general context. In Basic Writing subject, they need minimum requirements in writing that cover spelling and diction to be conveyed in sentences or even paragraph. They are also expected to be able to write simple sentence to complex sentence and produce different genre of paragraph writing, i.e. exposition, narration, and description. 2) Generally, the students‟ lack in writing is generating supporting sentences to be developed in an academic paragraph. 3) The materials that have been developed are arranged in eight chapters that cover about simple sentence to complex sentence, topic sentence, controlling idea, and supporting sentences, concluding sentence and outline, developing simple academic paragraph, review and revise paragraph, descriptive paragraph, recount paragraph, and peer-editing. 4) The module is facilitated by Android application as the supplement. The eligibility level of the product from media expert is 80.95 that includes in Good category; meanwhile, the eligibility level of the product from material expert is 96.19 that includes in Very Good category. Data from students‟ response towards the product of this study is 85.40 that includes in Very Good category.